Regulating T Cell Population Alleviates SLE by Inhibiting mTORC1/C2 in MRL/lpr Mice - Dongya Zhang; Meiling Wang; Guoping Shi; Peng Pan; Jianjian Ji; Jianjian Ji; Pengfei Li (Frontiers Media S.A., 2021)
It's well known that the mammalian target of rapamycin (mTOR) exerts a critical role in the regulator of immune cells and is associated with T cells dysfunction in patients with systemic lupus erythematosus (SLE). Antigen-induced T-cell proliferation via mTORC1 suppressed by Rapamycin has been used to improve SLE primarily. Previously it has showed that INK128, a highly potent, specific orally inhibitor of mTORC1 and mTORC2, significantly attenuates SLE in pristine-induced lupus mice. Herein we compared the cure effects of INK128 and rapamycin on lupus mice. We treated MRL/lpr mice with INK128 or rapamycin at 12 weeks-age. The effect of the two inhibitors on the lupus mice was determined by immunohistochemistry. The effect of the two inhibitors on T cell populations was investigated by flow cytometry. The mTOR signaling was measured by Western Blot. INK128 remarkably alleviated SLE by reducing splenomegaly, renal inflammation and damage, and resuming T-cell dysfunction. The more effective of INK128 on SLE than rapamycin. INK128 effectively suppressed mTORC1 and mTORC2 activity in T cells, but rapamycin just suppressed mTORC1 activity. Thus, our results show that INK128 is can effectively alleviate SLE and be used as one of the potential clinical therapeutic candidates for SLE.